PENGARUH KEPUASAN KERJA, KOMITMEN ORGANISASIONAL DAN MOTIVASI KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Putra, I Putu Adi Kususma; Sudibya, I Gede Adnyana (E-Jurnal Manajemen; Vol 7 No 8 (2018), 2018)
The purpose of this study is to determine the effect of job satisfaction, organizational commitment, and work motivation of organizational citizenship behavior in LPD Tanjung Benoa. The population in this research is all employees in LPD Tanjung Benoa which amounted to 32 people. The sample used in this study is the entire population of 32 people with the participation of leaders. By the method of determining saturated sampling is the technique of determining the sample when all members of the population used as a sample. This research uses multiple linear regression analysis to test the effect of job satisfaction, organizational commitment and work motivation to OCB in LPD Tanjung Benoa. The results showed that job satisfaction, organizational commitment and work motivation had a positive and significant effect on OCB employees in LPD Tanjung Benoa. That is, the higher job satisfaction, organizational commitment and work motivation owned by employees, it will increase the OCB LPD employees Tanjung Benoa.